Indonesian Language as a Means of Positive Student Character Building: Bahasa Indonesia sebagai Sarana Pembentukan Karakter Positif Siswa - Saprudin, Rika Fauziyah; Giovanni, Alvina; Herlina, Nina; Kusmana, Suherli (Universitas Muhammadiyah Sidoarjo, 2025)
Indonesian language learning in elementary schools not only aims to improve language skills, but also serves as a character building tool for students. This study aims to describe the role of Indonesian language learning in students' character building and identify the teacher's strategy as a teacher in integrating character values. The approach used was descriptive qualitative through total sampling technique involving all fourth grade students at SDN 2 Sitiwinangun. Data were collected through interviews, observation and documentation, then analyzed using the Miles and Huberman model. This model includes data reduction, data presentation, and conclusion drawing. The results of this study show that Bahasa Indonesia contributes greatly to character building. As many as 84% of students stated that this learning teaches honesty, 89% assessed that teachers emphasize good manners, and 79% said that reading texts are full of good values. The strategies used by teachers include modeling (79%), giving meaningful tasks (74%), educational reprimands (68%), and habituation of polite language (63%). The results of this study show that Indonesian language learning is effective in shaping students' positive character through the integration of moral values in the learning process, so that it becomes an important provision in social and community life. Highlights: Indonesian lessons instill honesty, manners, and moral values. Teachers use modeling, tasks, and polite language habits. Language learning supports students’ social development. Keywords: Indonesian Language Learning, Character Building, Elementary Education, Teacher Strategies, Moral Values